2019
DOI: 10.2174/0929867326666190104165311
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum, Gallium and their Impact on Oxidative Stress

Abstract: The role metals play in living organisms is well established and subject to extensive research. Some of them participate in electron-exchange reactions. Such reactions cause generation of free radicals that can adversely impact biological systems, as a result of oxidative stress. The impact of ‘non-biological’ metals on oxidative stress is also a worthy pursuit due to the crucial role they play in modern civilization. Lanthanides (Ln) are widely used in modern technology. As a result, human exposure to them is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…If the anticancer agent eliminates the O 2 •− at pH of 7.45, this protects healthy cells from malignization. Ga(III)-containing compounds are promising anticancer agents [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], the metal ion being responsible for the toxicity against malignant cells [ 24 , 25 , 26 , 27 ]. The Ga(III) complex of 5-aminoorotic acid proved to be a better antioxidant than the ligand itself at normal homeostatic pH [ 39 , 40 ], but its interaction with O 2 •− at this pH was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the anticancer agent eliminates the O 2 •− at pH of 7.45, this protects healthy cells from malignization. Ga(III)-containing compounds are promising anticancer agents [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], the metal ion being responsible for the toxicity against malignant cells [ 24 , 25 , 26 , 27 ]. The Ga(III) complex of 5-aminoorotic acid proved to be a better antioxidant than the ligand itself at normal homeostatic pH [ 39 , 40 ], but its interaction with O 2 •− at this pH was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Since cancer cells require iron in larger quantities, compared to normal cells [ 24 ], the introduction of Ga(III) in order to disrupt the iron-dependent metabolic pathways [ 25 ] in malignant cells seems a promising strategy in cancer treatment [ 26 ]. Ga(III) salts are well known anticancer agents [ 27 , 28 ]. Simple gallium salts such as gallium nitrate, gallium chloride, and gallium citrate have been investigated for their antitumor, anti-inflammatory, and antimicrobial properties [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of REE elements play a role in the electron-exchange reactions in living organisms, causing the generation of free radicals that affect biological processes, e.g., oxidative stress [ 29 ]. In the previous study, it was demonstrated that REEs had a hormetic effect on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Successful transport of lanthanide ions to the tumor has to be accompanied by some kind of mechanism to avoid their detrimental effect on healthy cells. These somewhat contradicting requirements characterize the search for new coordination compounds with improved antitumor activity and protective effects on normal cells [ 44 , 45 ]. One possible solution would be to use a coordination complex, comprising a highly pro-oxidant lanthanide cation, surrounded by bioactive ligands with antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%